2021
DOI: 10.2106/jbjs.cc.20.00694
|View full text |Cite
|
Sign up to set email alerts
|

Bicompartmental Bucket Handle Meniscal Tear with Chronic ACL Deficiency Causing a Rare Triple PCL and Triple Cruciate Sign

Abstract: Case: A 16-year-old football player presented with chronic ACL deficiency along with bicompartmental bucket handle meniscal tears. Conclusion: We present a “triple cruciate” sign in addition to the triple posterior cruciate ligament (PCL) sign seen on Magnetic Resonance Imaging (MRI) to aid in diagnosing this injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Simultaneous occurrence of bucket handle tears of both menisci of the same knee is a rare occurrence with interesting and seldom viewed signs on MRI imaging. Few case reports of the same have been published in the literature ( Table 1 ) which shows that a sudden complex twisting injury of the knee results in this condition [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In our case, the patient fell from a height, probably twisting his knee with the torque tearing both menisci of his left knee.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneous occurrence of bucket handle tears of both menisci of the same knee is a rare occurrence with interesting and seldom viewed signs on MRI imaging. Few case reports of the same have been published in the literature ( Table 1 ) which shows that a sudden complex twisting injury of the knee results in this condition [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In our case, the patient fell from a height, probably twisting his knee with the torque tearing both menisci of his left knee.…”
Section: Discussionmentioning
confidence: 99%
“…Koukoulias et al [ 7 ] reported a case with an accompanying medial cruciate ligament tear, while Lykissas et al [ 8 ] discussed a case with an associated chondral lesion of the medial femoral condyle with the latter resembling the finding in the index case. The youngest patient reported was a 16-year-old male reported by Sales et al [ 1 ] and the oldest were aged 38 years Koukoulias et al [ 7 ] and Wright et al [ 9 ]. Our patient is 1 year older.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation